The effects of influential behavioural factors on investors’ decision making in stock market of Pakistan - Sadiq, Misbah (2015)
The objective of this study is to investigate the relationship between behavioural factors affecting individual investors’ decision behaviour while investing in the capital stock market. To achieve this objective, the study has tested the relationship of firm’s specific attributes and personality traits of individual investors in the stock market of Pakistan. In addition, this study has examined the mediating effect of sensational attitude between (1) firm’s specific attributes and investment decision behaviour and (2) personality traits and investment decision behaviour. Furthermore, this study also investigates the moderating effect of brand familiarity on the relationship between firm’s specific attributes and sensational attitude. In this study, the positivist research approach has been used and survey methodology has been adopted to collect responses from individual investors of capital markets of Pakistan. The purposive probability sampling technique was employed and about five hundred questionnaires were distributed while four hundred fifty responses were returned and were used in the present study. Structural equation modeling techniques were applied to analyze the data. Findings indicate that firm’s specific attributes and personality traits were found positive and significant predictors of investment decision behaviour. Additionally, sensational attitude was found to have a significant mediating role between firm’s specific attributes, personality traits and investment decision behaviour. Besides, brand familiarity was found as a moderator on the relationship between firm’s specific attributes and investment decision behaviour. The results highlight that both firm’s specific attributes and personality traits are essential in the investment decision behaviour among individual investors of the Pakistani stock market. As there are limited studies about behavioural finance in Pakistan, therefore, this study will contribute significantly to the development of capital market of Pakistan.